The positive effects of priming exercise on oxygen uptake kinetics and high-intensity exercise performance are not magnified by a fast-start pacing strategy in trained cyclists - Aparecido Correa Carita, R.; Coelho Greco, C.; Denadai, B. S. (PLOS ONE, 2014)
The purpose of this study was to determine both the independent and additive effects of prior heavy-intensity exercise and pacing strategies on the VO2 kinetics and performance during high-intensity exercise. Fourteen endurance cyclists (VO2max = 62.8±8.5 mL.kg-1.min-1) volunteered to participate in the present study with the following protocols: 1) incremental test to determine lactate threshold and VO2max; 2) four maximal constant-load tests to estimate critical power; 3) six bouts of exercise, using a fast-start (FS), even-start (ES) or slow-start (SS) pacing strategy, with and without a preceding heavy-intensity exercise session (i.e., 90% critical power). In all conditions, the subjects completed an all-out sprint during the final 60 s of the test as a measure of the performance. For the control condition, the mean response time was significantly shorter (p<0.001) for FS (27±4 s) than for ES (32±5 s) and SS (32±6 s). After the prior exercise, the mean response time was not significantly different among the paced conditions (FS = 24±5 s; ES = 25±5 s; SS = 26±5 s). The end-sprint performance (i.e., mean power output) was only improved (~3.2%, p<0.01) by prior exercise. Thus, in trained endurance cyclists, an FS pacing strategy does not magnify the positive effects of priming exercise on the overall VO2 kinetics and short-term high-intensity performance.